Flecainide and risk of skin neoplasms: Results of a large nested case–control study in Spain and Denmark - Reyes, Carlen; León-Muñoz, Luz M; Pistillo, Andrea; Jóhannesdóttir Schmidt, Sigrún Alba; Kristensen, Kasper Bruun; Puente, Diana; LLorente-García, Ana; Huerta-Álvarez, Consuelo; Pottegård, Anton; Duarte-Salles, Talita (Frontiers in Pharmacology, 2022)
Background: A previous study in Denmark suggested an increased melanoma risk associated with the use of flecainide. Objective: To study the association between flecainide use and the risk of melanoma and non-melanoma skin cancer in Spain and Denmark. Methods: We conducted a multi-database case-control study in (database/study period) Spain (SIDIAP/2005-2017 and BIFAP/ 2007-2017) and Denmark (Danish registries/ 2001-2018). We included incident cases of melanoma or non-melanoma skin cancer (NMSC) aged ≥18 with ≥ 2 years of previous data (≥10 years for Denmark) before the skin cancer and matched them to controls (10:1 by age and sex). We excluded persons with immunosuppression or previous cancer. We defined ever use as any prescription fill and high-use as a cumulative dose of at least 200g (reference: never use). We categorised cumulative dose for dose-response assessment. We used conditional logistic regression to compute ORs (95% CI) adjusted for photosensitising, anti-neoplastic, disease-specific drugs, and comorbidities. Results: The total numbers of melanoma/NMSC cases included were: 7,809/64,230 in SIDIAP, 4,661/31,063 in BIFAP and 27,978/152,821 in Denmark. In Denmark, high use of flecainide was associated with increased adjusted ORs of skin cancer compared with never use [melanoma: OR 1.97 (1.38-2.81); NMSC: OR 1.34 (1.15-1.56)]. In Spain, an association between high use of flecainide and NMSC was also observed [BIFAP: OR 1.42 (1.04-1.93); SIDIAP: OR 1.19 (0.95-1.48)]. There was a non-significant dose-response pattern for melanoma in Denmark and no apparent dose-response pattern for NMSC in any of the three databases. We found similar results for ever-use of flecainide. Conclusions: Flecainide use was associated with an increased risk of melanoma (Denmark only) and NMSC (Denmark and Spain) but without substantial evidence of dose-response patterns. Further studies are needed to assess for possible unmeasured confounders.